Analisis Pengaruh Financing To Deposit Ratio (FDR), Beban Operasional Pendapatan Operasional (BOPO), Capital Adequacy Ratio (Car), Net Operating Margin (NOM) Terhadap Return On Equity Pada PT. KB Bukopin Syariah Pada Tahun 2015-2023 - Hayati, Tri Sela (PROGRAM STUDI EKONOMI ISLAM PROGRAM PASCASARJANA IAIN SULTAN MAULANA HASANUDDIN BANTEN, 2024)
This research was conducted to determine the effect of Operational Costs on Operational Income (BOPO), Capital Adequacy Ratio (CAR) and Financing To Deposit Ratio (FDR), Net Operating Margin (NOM) on profitability as measured by Return On Equity as a research variable. The sample in this research is Bukopin Syariah's quarterly financial report for the 2015-2022 period. The sampling method used was a purposive sampling method so that 32 samples were obtained. The method used in this research uses the Error Correction Model method with a quantitative approach. The results of this research state that partially the Ratio (FDR) variable does not have a significant effect on ROE at PT. KB Bukopin Syariah, Operational Costs to Operating Income (BOPO) has a positive influence on ROE. PT. KB Bukopin Syariah, then the CAR (CAR) variable does not have a positive effect on PT's ROE. KB Bank Bukopin Syariah, the NOM variable has a positive influence on ROE, while overall the FDR, BOPO, CAR, NOM and ROE variables have a significant influence.